Immanent Domain: Pervasive Computing and the Public Realm. - Cuff, Dana (Journal of Architectural Education, 2003)
A wave of emergent digital technology holds vast implications for the public sphere. Indeed, these new forms of mobile and ubiquitous systems, called pervasive computing, challenge some of our fundamental ideas about subjectivity, visibility, space, and the distinction between public and private. Together, these challenges reformulate our conception of the civic realm. From cell phones to wireless local area networks, smart buildings to embedded vehicular computers, an invisible web of digital technology already lies across the visible world creating new space for work, data, advertisement, investigation, communication, intimacy, and danger. This generation of computers is so well integrated with the environment that it will be difficult to distinguish between the two, which represents a profound transformation for everyday life.